The Influence of Discipline and Work Motivation on Employee Performance with Job Satisfaction as Mediation at PT. Jasiyah Travel Service - Asmin Jaya; Rabihatun Idris; Hardiani Hardiani (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This study seeks to investigate how work discipline, work motivation, and job satisfaction impact employee performance directly. It also examines the direct influence of work discipline and work motivation on job satisfaction. The study looks into the indirect impact of work discipline and work motivation on employee performance, with job satisfaction acting as a mediator. Data was collected through questionnaires from a sample of 32 respondents at PT. Jasiyah Travel Service. The questionnaire results were analysed for validity and reliability using the PLS model scheme. Several tests were conducted to evaluate the model, including determinant coefficient tests, goodness of fit tests, and hypothesis tests. SmartPLS version 3 was used for data processing. The study found that work discipline and job satisfaction positively impact employee performance. Work discipline also has a positive effect on job satisfaction. However, work motivation does not affect employee performance or job satisfaction. Work discipline was found to indirectly influence employee performance through job satisfaction as a mediator, while work motivation did not have the same effect.